Behavior change counseling (BCC) by frontline health workers (FHW) and a mass media campaign improved complementary feeding (CF) practices more than mass media alone in rural Bangladesh - Saha, Kuntal K.; Rawat, Rahul; Khaled, Adiba; Ruel, Marie T.; Menon, Purnima (Wiley, 2013)
We assessed the effects of combining a mass media campaign with BCC by FHW on CF practices in Bangladesh. Survey data were collected from randomly sampled households with children 6–23 mo in 2010 (baseline; N=250 per group) and 2012 (mid‐point; N=230 per group) from 10 sub‐districts cluster‐randomized to either an intensive (FHW + mass media) or a non‐intensive (mass media only) intervention. Exposure to FHW and television spots (TVS) on 6 child feeding themes was measured using aided recall methods. CF practices were measured using WHO‐recommended indicators. In 2010, home visits by FHW and prevalence of optimal CF practices were very low with no significant differences between study areas. In 2012, home visits by FHW were significantly higher in intensive (60%) than in non‐intensive (17%) areas. Percentage of mothers who received advice from FHW on IYCF was 2.5 times higher in intensive areas. In both areas, 20–50% of mothers saw the TVS on 6 themes. Significantly higher proportions of children in intensive areas achieved minimum diet diversity (p<0.01) and minimum acceptable diet (p<0.05), and consumed iron rich foods (p<0.001) than in non‐intensive areas. At this 2‐y time point in the study, mothers who received both FHW counseling and mass media had significantly better CF practices than those who were exposed to mass media only. Funded by Bill & Melinda Gates Foundation, through Alive & Thrive, managed by FHI360.